Active Fault Tolerant Control for Unmanned Underwater Vehicle With Sensor Faults - Wang, Xianghua (IEEE transactions on instrumentation and measurement, 2020)
In this article, we propose an active fault tolerant control (FTC) scheme to achieve trajectory tracking for unmanned underwater vehicle (UUV) subject to sensor faults and multiple uncertainties (including external disturbances and modeling errors). To make matters more challenging, it is assumed that the velocities (linear and angular) are unavailable. The proposed active FTC scheme includes a fault detection and isolation (FDI) unit and an FTC unit. The FDI is performed by an adaptive interval observer whose parameters are determined automatically by adaptive laws, relaxing the requirement on the bound of uncertainty. The FDI mechanism is if an output error exceeds its upper and lower bound estimates, then an alarm implying the corresponding sensor has a fault will be triggered. If the sensor is healthy, then the nominal controller is still adopted; otherwise, an FTC unit (where the real output of the faulty sensor is estimated as a linear representation of its upper and lower bounds) will be constructed to ensure the acceptable tracking performance of the faulty system. Finally, a simulation example is used to prove the efficacy of the proposed scheme.